Seasonal Occurrence of a Predaceous Mite Amblyseius addoensis Van der Merwe & Ryke (Acari: Phytoseiidae) on Table Grapes - Schwartz, A. (South African Journal of Enology and Viticulture, 2017)
Predaceous mites (Phytoseiidae) and their importance as biological control agents, especially in fruit tree culture, are well documented. These mites are primarily predators of the Tetranychidae. Amblyseius addoensis Van der Merwe & Ryke was first identified on vines in 1964 (Van der Merwe & Ryke, 1964). Dennill (1986) recorded the presence of A. addoensis, along with other predators, in growth buds during a study of the vine bud mite, Colomerus vitis (Pagst.). During the course of a recent study on the seasonal occurrence of thrips ( Thrips tabaci Lindeman) in vineyards in the Western Cape, A. addoensis was found in leaf samples and this presented an opportunity to investigate the seasonal occurrence of this mite.